Inducers, Attractors and Modulators of CD4+ Treg Cells in Non-Small-Cell Lung Cancer - Xie, Mengxiao; Wei, Jia; Xu, Jian (Frontiers in Immunology, 2020)
Lung cancer is the leading cause of cancer-associated deaths worldwide, with non-small cell-lung cancer (NSCLC) accounting for approximately 80% of cases. Immune escape has been demonstrated to play a key role in the initiation and progression of NSCLC, although the underlying mechanisms are diverse and their puzzling nature is far from being understood. As a critical participant in immune escape, the CD4+ T cell subset of regulatory T (Treg) cells, with their immunosuppressive functions, has been implicated in the occurrence of many types of cancers. Additionally, therapies based on Treg blockade have benefited a portion of cancer patients, including those with NSCLC. Accumulating literature has noted high Treg infiltration in NSCLC tumor tissues, bone marrow, lymph nodes and/or blood; moreover, the tumor milieu is involved in regulating the proliferation, differentiation, recruitment and suppressive functions of Treg cells. Multifarious mechanisms by which CD4+ Treg cells are generated, attracted and modulated in the NSCLC milieu will be discussed in this review.